Assessing Glyphosate and Fluridone Concentrations in Water Column and Sediment Leachate - Pandey, Pramod; Caudill, Jeffrey; Lesmeister, Sarah; Zheng, Yawen; Wang, Yi; Stillway, Marie; Hoffmann, Krista; Gilbert, Patricia; Kwong, Michael; Conrad, Louise; Teh, Swee (Frontiers in Environmental Science, 2019)
In recreational water bodies, herbicides are widely used for controlling unwanted weeds, and impacts of herbicide residues on health risks to aquatic ecosystem is a serious concern. This study was aimed to improve the existing understanding of the deposition of herbicides from water column to bed sediment and leachate of herbicides from bed sediment to water column. We investigated the attachment of two herbicides with sediment and release from sediment: 1) Glyphosate; and 2) Fluridone. The goal of this study was to determine the deposition and release of Glyphosate and Fluridone in bed sediment of the Sacramento–San Joaquin River Delta. Field sampling was performed to collect water and sediment samples from Sacramento–San Joaquin River Delta. Bottom dredge sampler was used for collecting sediment samples and horizontal water bottle sampler was used for collecting water samples. A series of experiments were conducted to determine the attachment and release of Fluridone and Glyphosate from sediment at a different level of initial concentrations. For analyzing Fluridone and Glyphosate in sediment leachate and water, samples were processed using enzyme-linked immunosorbent assay (ELISA) based method. Observations showed that proportions of Glyphosate concentrations in water were higher than Fluridone concentrations in water, when both herbicides were inoculated in water in same quantity. On the contrary, the concentrations of Fluridone in sediment-bound leachate were higher than Glyphosate concentrations in sediment-bound leachate, regardless of the initial concentrations. Fluridone and Glyphosate concentrations in water column samples differed significantly (p < 0.05) over the time even initial concentrations of these herbicides were kept similar, which indicates that Fluridone interaction with water column was considerably different than the interaction of Glyphosate with the water column. Bed sediment can be an important sink and source for release of Fluridone and Glyphosate from bed sediment to the water column of an ambient water body. Significant concentrations of herbicides were deposited in bed sediment of Sacramento-San Joaquin Delta, and eventually the high concentrations of herbicides were observed in sediment leachate.